Private School Marketing Strategy as Anticipation for Lack of Students - Ardhiana Puspitacandri, Sutoyo, U. Widyaningsih, Arleyni, A. A. I. Sri Wahyuni, Ahmad Fudholi (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to determine the marketing strategies used by private vocational schools in an effort to increase the number of students. This type of research uses content analysis with descriptive qualitative methods. This study uses primary sources based on interviews with principals and teachers, and secondary data sources, including documents and existing literature. Data analysis uses the Miles and Huberman Model, which consists of data collection, data reduction, data display and verification. The tests used for the validity of the data in this study are expert and practitioner tests, as well as source and technique triangulation. Karanganyar has 23 private SMKs that have a variety of students. The number of schools that have closed down due to low enrolment has increased. Thus, private vocational schools must consider certain factors to maintain and increase the number of students using marketing strategies. The results of the marketing strategy analysis of 23 private SMKs in Karangnyar have shown that only one private SMK has a sound product strategy. A new consumer strategy is implemented by six private SMKs, and the lock-in strategy system used by the majority of private SMKs in Karangnyar still relies on their alumni.